Corporate Diversification and Stock Price Crash Risk: Do Female Directors Matters? Evidence From Malaysia - Kian-Tek Lee (Asian Academy of Management Journal of Accounting and Finance, 2022)
This study examines the relation between corporate diversification and stock price crash risk and whether female directors moderate this relation. Using a sample of Malaysian publicly listed firms based on 2010–2016 data, our study finds diversification mitigates crash risk but only for highly diversified firms. Our study also finds that the mitigating effect of diversification is more pronounced for firms with higher proportion of female directors in the board in which it is aligned with the notion of gender diversity in promoting good corporate governance. Our findings are beneficial to stock investors in managing the “tail risk” in stock prices of conglomerates/diversified firms.